ANOMALIES OF COMPLEX VARIATIONAL PHASE-SHIFTS - Adhikari, S. K. (Elsevier B.V., 1992)
It is argued, contrary to various claims and expectations, that the phase shifts calculated via variational principles for the t matrix involving complex algebra may exhibit anomalous behavior. These anomalies are numerically demonstrated in the case of the complex Kohn and the Newton variational principles for the t matrix and are expected to appear for other similar variational principles for the t matrix, such as the Takatsuka-McKoy variational principle.